INTERNALISASI NILAI HUKUM PIDANA ISLAM DALAM HUKUM POSITIF DI INDONESIA (STUDI ANALISIS TINDAK PIDANA KESUSILAAN DALAM KUHP BARU DAN REGULASI DI LUAR KUHP) - Royani, Yayan Muhammad (Gapenas Publisher, 2024)
The process of internalizing the value of Islamic Criminal Law in positive law in Indonesia has been going on since before independence, especially in the civil field through religious courts. In the criminal field, the values of Islamic Criminal Law related to moral crimes are reflected in the articles of the Criminal Code, although they are not fully accommodated. Several articles such as Article 281 on public morality, Article 282 on the dissemination of pornography, Article 284 on adultery, and Article 285 on rape show relevance to the concepts of takzir and limit in Islamic Criminal Law. The new Criminal Code expands the internalization of these values, as seen in Article 406 concerning morality in public, article 407 concerning pornography, Articles 408-410 concerning contraception, Article 412 concerning gathering, and Article 414 concerning same-sex molestation. Article 114 on adultery also accommodates the concept of limits for perpetrators, both married and single. The reforms in the new Criminal Code show a balance in protecting societal values that are in line with the principles of Islamic law.